COVID-19-related health anxieties and impact of specific interventions in patients with inflammatory bowel disease in the UK. Issue 3 (11th September 2020) - Mir, Nasir; Cheesbrough, Jonathan; Troth, Thomas; Hussain, Nasir; Hopkins, Laurence Joseph; Shi, Jiaqi; Sarker, Najiat; Smith, Emma; Courtney, Finula; Flaherty, Jill; Hill, Rebecca; Jebb, Sarah; et al.
Abstract : Objective: Health-related concerns brought on by the COVID-19 pandemic and the impact of specific local and national interventions have not been explored in patients with inflammatory bowel disease (IBD) in the UK. We evaluated perspectives of patients with IBD on the pandemic and effectiveness of information dissemination in addressing concerns. Methods: We prospectively conducted a survey among patients with IBD during the COVID-19 pandemic to assess concerns, information-seeking behaviours, risk perception, compliance and effect of specific interventions. Results: A total of 228 patients were interviewed of whom 89% reported being concerned about the impact of COVID-19 on their health. Access to at least one IBD-specific clinical interaction during the pandemic (COVID-19 information letter from IBD team, interaction with IBD team or general practitioner, Crohn and Colitis UK website visit) was significantly associated with alleviating concerns (OR 2.66; 95% CI 1.35 to 5.24; p=0.005). Seeking health information solely through unofficial channels (search engines or social media) was less likely to ease concerns (OR 0.15; 95% CI 0.03 to 0.61; p=0.008). A quarter of patients disagreed with their assigned risk groups, with majority perceiving higher-risk profiles. This discordance was greatest in patients within the moderate-risk group and constituted immunosuppression use. Nearly 40% of patients had ongoing concerns with regard to their medications of whom a third felt their concerns were not addressed. Conclusion: IBD-specific clinical interactions are associated with alleviation of COVID-19 health concerns. These findings have wider implications and emphasise importance of innovative solutions that facilitate effective communication with patients without overburdening current services.